CHEMICAL AND ELEMENTAL COMPOSITION OF TRIBULUS TERRESTRIS (PUNCTURE VINE,) GROWING IN FERGANA REGION (FERGANA CITY, BUVAYDA DISTRICT), AND ITS ROLE IN TRADITIONAL MEDICINE (Scientific journal of the Fergana State University, 2026)
This article focuses on the significance and chemical composition of the plant Tribulus terrastris, known locally as “temirtikan,” in folk medicine. Research has revealed that this plant, from its body to its roots, possesses therapeutic properties. The biological active compounds, such as saponins, flavonoids, and alkaloids, are particularly responsible for its medicinal effects. The article also describes the methods of using Tribulus terrastris for treating joint pain in adults. Its widespread availability and valuable properties make this plant a crucial resource for both modern pharmacology and traditional medicine. The findings of this study provide a foundation for developing new plant-based medicinal products.